Desenvolvimento de sistemas líquido cristalinos lamelares contendo diferentes concentrações de Ac-Wahx-kttks para o tratamento do envelhecimento cutâneo - Martinelli, Ariane Migliato [UNESP] (2015)
During the last decade there has been great interest in lyotropic liquid crystalline systems, being used to the release systems of biologically active agents, the cosmetic, chemical and pharmaceutical industries. One reason for this is that the lyotropic liquid systems exist in many parts of the body such as brain, muscle, retina and many others and their special structure plays an important role in vital movements. Skin aging is a result of intrinsic and/or extrinsic processes. The skin changes resulting from these processes include dyschromia, roughness, fine and persistent wrinkles followed by deeper wrinkles. Among several peptide subfragments of the KTTKS was found to be the minimum sequence necessary to stimulate collagen production by 80% and fibronectin in a variety of mesenchymal cells. Due to the stimulation of collagen synthesis, the KTTKS has attracted great attention as a cosmetic ingredient to provide anti-aging effects. Thinking about all these issues, this master's work aimed to the preparation of lamellar liquid crystalline systems containing different concentrations of Ac-Wahx-KTTKS peptide which has physico-chemical properties that will improve its permeation through the skin. Ac-WAhx-KTTKS peptide was obtained in a purity above 99.97%. The polarized light microscopy and X-ray scattering the low angle allowed to assess that after the incorporation of the peptide did not change phases of the systems, remaining in the lamellar phase. The rheology showed that even after the incorporation of the peptide, the systems continued to show thixotropic (with the exception of formulations F1, F1A and F1B), non-Newtoniano behavior and shear thinning profile. The biosynthesis of collagen in vitro test showed that the peptide is effective in the treatment of skin aging, increasing to 80% in collagen production by fibroblasts. The in vitro tests to the assessment of the release of Ac-Wahx-KTTKS in the formulations showed that the ...